2014
DOI: 10.1080/00288233.2014.941508
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effects of dicyandiamide (DCD) on nitrogen cycling and dry matter production in a 3-year trial on a dairy pasture in South Otago, New Zealand

Abstract: The nitrification inhibitor dicyandiamide (DCD) has been reported to significantly reduce nitrate (NO À 3 ) leaching and nitrous oxide (N 2 O) emissions under urine patches in New Zealand trial conditions. However, results on the efficacy of DCD for increasing pasture production have been inconclusive. As part of a national series of nitrous oxide mitigation research (NOMR) trials, a 3-year study was conducted at a dairy farm in South Otago to examine the effect of DCD on pasture production and N leaching unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…2; Table 2). Similar findings on the effectiveness of broadcasting DCD at 10 kg ha −1 for reducing N 2 O emissions have been reported in other studies (e.g., de Klein et al 2011;Luo et al 2013;Cameron et al 2014;de Klein et al 2014;Kim et al 2014;Ledgard et al 2014). Ledgard et al (2008) developed a novel-patented approach to strategic application of DCD to urine patches by directly administering the DCD to animals.…”
Section: Urine Application and N 2 O Emissionssupporting
confidence: 89%
See 2 more Smart Citations
“…2; Table 2). Similar findings on the effectiveness of broadcasting DCD at 10 kg ha −1 for reducing N 2 O emissions have been reported in other studies (e.g., de Klein et al 2011;Luo et al 2013;Cameron et al 2014;de Klein et al 2014;Kim et al 2014;Ledgard et al 2014). Ledgard et al (2008) developed a novel-patented approach to strategic application of DCD to urine patches by directly administering the DCD to animals.…”
Section: Urine Application and N 2 O Emissionssupporting
confidence: 89%
“…As discussed earlier, DCD is subject to degradation and leaching from the surface soil where urine has accumulated and N 2 O is being produced, leading to lower efficiency of DCD use (Luo et al 2008;Shepherd et al 2012;Kelliher et al 2014). Compared with the southern part of country, DCD would be less effective in the northern North Island of New Zealand, where the present study was conducted, due to warmer soil temperatures in winter de Klein et al 2014;Kim et al 2014;Ledgard et al 2014), as an increase in soil temperature has been shown to decrease the efficacy of DCD (Puttanna et al 1999). As well, the current study was conducted on a free-draining volcanic soil, which has naturally high rates of nitrification (Sarathchandra 1978) and rainfall/ drainage levels that are generally higher than those in many other dairying regions.…”
Section: Dcd Application Ratementioning
confidence: 89%
See 1 more Smart Citation
“…Flux calculations (unit: ng N g − 1 dry soil h − 1 ) were based on the assumption that there was a linear increase in the N 2 O concentration with time in the closed chamber. The procedure followed was the same as in numerous recently published studies (de Klein et al, 2014;Lessa et al, 2014;Martins et al, 2015;Cardoso et al, 2016;Nichols et al, 2016;van der Weerden et al, 2016). The lowest detection limit was found using linear regression (see Parkin et al, 2012), which was compared to the quadratic methods of Hutchinson/Mosier and revised Hutchinson/Mosier.…”
Section: N 2 O Measurement and Soil Analysismentioning
confidence: 99%
“…The number of studies quantifying N 2 O emissions from dung treated with nitrification inhibitors is small; however, our analysis of 39 observations suggested a mean reduction of 63% in N 2 O EF for cattle dung. Again, temperature is a key variable, with temperate New Zealand studies showing a reduction (e.g., Cameron et al., 2014; de Klein et al., 2014), whereas Brazilian studies under a subtropical climate showed limited effectiveness (Simon et al., 2018).…”
Section: Discussionmentioning
confidence: 99%